2018
DOI: 10.5123/s1679-49742018000400002
|View full text |Cite
|
Sign up to set email alerts
|

Triagem auditiva de crianças com síndrome congênita pelo vírus Zika atendidas em Fortaleza, Ceará, 2016

Abstract: Objective: to describe the results of hearing screening performed in children with Congenital Zika Virus Syndrome (CZS) in Fortaleza, Ceará, Brazil. Methods: this was a descriptive cross-sectional study involving children with CZS receiving health care in Fortaleza, 2016; the hearing screening tests performed were immittance audiometry, transient otoacoustic emissions (TOAE), acoustic reflexes, and cochleopalpebral reflex (CPR). Results: The study included 45 children with an average age of 10 months. 44 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
5
0
6
Order By: Relevance
“…Considering the age of evaluation of these cases (between 30 to 42 months), the prevalence can be considered high [ 32 ]. This outcome was also that reported in the study by Leite et al [ 33 ] and may be indicative of altered immune responses and/or the presence of structural changes in the middle ear, raising the possibility that CZVI is a predisposing factor for this occurrence.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the age of evaluation of these cases (between 30 to 42 months), the prevalence can be considered high [ 32 ]. This outcome was also that reported in the study by Leite et al [ 33 ] and may be indicative of altered immune responses and/or the presence of structural changes in the middle ear, raising the possibility that CZVI is a predisposing factor for this occurrence.…”
Section: Discussionsupporting
confidence: 86%
“…In another study conducted with a sample of 43 children with CZVS, there was an absence of responses in the TOAE in 13 of them 21 . With the TOAEs, it was possible to analyze the cochlear function quickly, objectively, and non-invasively; this procedure being very important in clinical practice to perform the crosscheck 20,26 .…”
Section: Discussionmentioning
confidence: 88%
“…As in Brazil, this infection evokes the need for studies that investigate various aspects of children's development, such as audiological assessment and monitoring of the affected population 10 . Few studies describing the effects of congenital infection on hearing with a significant sample can be found in the literature 8,12,21 . In the long run, new research results may contribute to the understanding of these problems.…”
Section: Discussionmentioning
confidence: 99%
“…All studies that performed ophthalmological evaluations exposed some alteration, such as microphthalmia, fundoscopic alterations, macular atrophy, optic nerve abnormalities, strabismus and visual acuity defects (12,14,27,36,45,50,51,56,60,61,67,68,(73)(74)(75)(76)(77)(78)(79). Twelve of 14 papers that evaluated audiological manifestations in children reported hearing disorders (11,14,27,36,37,39,43,51,56,60,62,64) and two did not observe any abnormalities (30,41).…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study, when evaluating 45 children with a mean age of 10 months, Leite et al ( 41 ) found no association between exposure to ZIKV during pregnancy and audiological alterations. Similarly, when comparing children exposed and not exposed to ZIKV, Fandiño-Cárdenas et al ( 30 ), in their cohort study of 66 exposed children did not observe hearing loss in the first two years of life.…”
Section: Discussionmentioning
confidence: 99%